Clinical and Laboratory Predictors of Elevated TRV In Sickle Cell Anaemia - Jane S. Afriyie-Mensah; Yvonne A Dei-Adomakoh; Audrey Forson; Martin Adadey; Thomas A. Ndanu; Joseph K. Acquaye (Journal of Hematology and Oncology Research, 2018)
Pulmonary hypertension (PH) has become an increasingly recognized complication in sickle cell anaemia (SCA) and is a major cause of morbidity and mortality. Though the burden of SCA in sub-Saharan Africa is high, there is paucity of data on SCA-associated PH with little or no attention given to it in routine patient care. The current study therefore sought to determine the prevalence of PH and its associated risk factors among adult patients with SCA. This was a cross-sectional study involving 76 clinically stable, hydroxyurea-naive participants. We obtained socio-demographic and clinical history. Measurement of Tricuspid Regurgitant jet Velocity (TRV) was obtained via transthoracic echocardiography and lung function was assessed using spirometry and pulse oximetry. Other investigations were complete blood counts, free plasma haemoglobin, serum urea and creatinine. Twenty-five (32.9%) of study participants had elevated TRV (≥ 2.5m/s) on Doppler echocardiography, which was suggestive of raised pulmonary artery systolic pressure. There were significant associations between elevated TRV and steady-state haemoglobin (p < 0.001), blood urea level (p = 0.030), presence of chronic leg ulcers (p = 0.043) and oxygen saturation (p < 0.001) and these may be identifiable and modifiable risk factors for selective screening with echocardiography in a resource poor setting.
Keywords: Sickle Cell Anaemia